2001
DOI: 10.1074/jbc.m007506200
|View full text |Cite
|
Sign up to set email alerts
|

Modified Phosphatidylethanolamine as the Active Component of Oxidized Low Density Lipoprotein Promoting Platelet Prothrombinase Activity

Abstract: We analyzed the influence of the atherogenic oxidized low density lipoproteins (LDL) on the activity of the platelet prothrombinase complex, a major contributor to overall thrombin formation in vivo. Platelet dependent thrombin generation was found to be strongly stimulated by in vitro oxidized LDL. The enhancement was additive to that observed with the platelet agonist thrombin. Oxidized LDL increased the platelet binding of annexin-V, suggesting that the augmented surface exposure of aminophospholipids promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…hand, aldehydes generated by the myeloperoxidase system of phagocytes were shown to covalently modify the amino groups of ethanolamine and serine glycerophospholipids to form biologically active Schiff base adducts (46). Zieseniss et al (38) found that Schiff base adducts between phosphatidylethanolamine and aldehydes in oxidized LDL provoke the stimulation of platelet prothrombinase activity. In the beginning, there was little consideration of the possibility that some of the masking of amino groups during LDL oxidation might be attributable to conjugation with phospholipid aldehydes, as exemplified by POVPC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…hand, aldehydes generated by the myeloperoxidase system of phagocytes were shown to covalently modify the amino groups of ethanolamine and serine glycerophospholipids to form biologically active Schiff base adducts (46). Zieseniss et al (38) found that Schiff base adducts between phosphatidylethanolamine and aldehydes in oxidized LDL provoke the stimulation of platelet prothrombinase activity. In the beginning, there was little consideration of the possibility that some of the masking of amino groups during LDL oxidation might be attributable to conjugation with phospholipid aldehydes, as exemplified by POVPC.…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning, there was little consideration of the possibility that some of the masking of amino groups during LDL oxidation might be attributable to conjugation with phospholipid aldehydes, as exemplified by POVPC. Several studies now exist that demonstrate covalent adduct formation between oxidized phospholipids and apoB (13,38,54). In this work, we found evidence that BODIPY-POVPE reacts with many cellular proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it has been previously established that GPEtn and GPSer lipids react with aldehydes (13-16), there have not been studies reporting the reaction of either of these aminophospholipids with acrolein. Furthermore, most of these previous aminophospholipid/aldehyde adduct studies have focused primarily on the formation of aldehyde-modified GPEtn and GPSer products in solution, and few studies have shown that these covalently modified GPEtn and GPSer species are present in cell membranes (17,18). …”
Section: Introductionmentioning
confidence: 99%